1998
DOI: 10.1084/jem.187.7.997
|View full text |Cite
|
Sign up to set email alerts
|

The Sequential Role of Lymphotoxin and B Cells in the Development of Splenic Follicles

Abstract: The transfer of lymphocytes into severe combined immunodeficiency (SCID) mice induces a series of histological changes in the spleen, including the appearance of mature follicular dendritic cells (FDCs). Studies were undertaken to clarify the role of lymphotoxin (LT) in this process. The results show that SCID mice have a small and partially differentiated white pulp containing marginal zone and interdigitating dendritic cells, but lacking FDCs. Transferred spleen cells can segregate into T and B cell areas sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
161
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(167 citation statements)
references
References 30 publications
5
161
0
1
Order By: Relevance
“…The positive regulatory roles of B cells extend to multiple immune system components; the absence of B cells during mouse development results in significant quantitative and qualitative abnormalities within the immune system, including a remarkable decrease in thymocyte numbers and diversity [12], significant defects within spleen dendritic cell and T cell compartments [13-15], absence of Peyer's patch organogenesis and follicular dendritic cell networks [16,17], and absence of marginal zone and metallophilic macrophages with decreased chemokine expression [15,17]. B cells also positively regulate lymphoid tissue organization [18,19]. Finally, dendritic cell, macrophage, and T H cell development may all be influenced by B cells during the formation of immune responses [20].…”
Section: Introductionmentioning
confidence: 99%
“…The positive regulatory roles of B cells extend to multiple immune system components; the absence of B cells during mouse development results in significant quantitative and qualitative abnormalities within the immune system, including a remarkable decrease in thymocyte numbers and diversity [12], significant defects within spleen dendritic cell and T cell compartments [13-15], absence of Peyer's patch organogenesis and follicular dendritic cell networks [16,17], and absence of marginal zone and metallophilic macrophages with decreased chemokine expression [15,17]. B cells also positively regulate lymphoid tissue organization [18,19]. Finally, dendritic cell, macrophage, and T H cell development may all be influenced by B cells during the formation of immune responses [20].…”
Section: Introductionmentioning
confidence: 99%
“…In SCID mice, which lack FDC as a result of the absence of mature B cells (29), the differentiation of FDC precursors into mature FDC can be induced within a few days after adoptive B cell transfer (30 -32). This induction is dependent on LT␣/LT␤R signaling by B cells, since it is not elicited by transfer of LT␣ Ϫ/Ϫ B cells (32). Thus, B cells from 1-wk-old naive BALB/c mice were tested for their capacity to generate FDC differentiation following their i.v.…”
Section: Neonatal B Cell-mediated Signaling To Fdc Precursorsmentioning
confidence: 99%
“…Subsequent studies established that host-derived DCs differentiate in the spleen of SCID mice after transfer of wild-type lymphocytes [8±10]. The recent elegant studies by Gonzalez et al [11] are even more relevant to the role of B lymphocytes in that they showed that B cells induce the appearance of DCs through the expression of membrane LT-a. These investigators observed that, following the transfer of B cells from membrane LT-a 1/1 but not LT-a 2/± , the expression of LT-a/2b on B lymphocytes, but not T lymphocytes, was critical for the formation of DC nettings.…”
mentioning
confidence: 99%